Blood cyst of the pulmonary valve: A case report - (:unkn) unknown (My University, 1999)
Blood-filled cysts of the heart valves are commonly reported at postmortem examination of infants but are rare in older children and adults. We present a case with blood cyst on the pulmonary valve that was surgically removed at the open heart operation. We also review the relevant literature.
Keywords: Blood cyst; Factor VIII; Pulmonary valve